6.5 Testing
6.5.1 More About Models: Two approaches for linear model
$ \[\begin{alignat}{2} Y &= E(Y) &&+ Y - E(Y) \\ &= \mu &&+ \epsilon \tag{Parameter-free approach } \\ \\ Y &= E(Y) &&+ Y - E(Y) \\ &= X \beta &&+ \epsilon \tag{Parameter approach} \end{alignat}\] $
$ \[\begin{alignat}{2} E(\epsilon) &= 0, \; \; \; && Cov(\epsilon) &&= \sigma^2 I \tag{Ordinary Least Square, OLS} \\ E(\epsilon) &= 0, && Cov(\epsilon) &&= \sigma^2 \Sigma \tag{Generalized Least Square, GLS} \end{alignat}\] $
- Consider
$ Y=X + , ; ; ; ; ; E()=0, ; Cov() = ^2 I $
\(\mathcal{C}(X)\) | \(\mathcal{C}(X)^\perp\) | |
---|---|---|
itslef | Estimation Space | Error Space |
orthogonal projection onto | \(M \\ = X(X'X)^-X'\) | \(I - M \\= I - X(X'X)^-X'\) |
\(E(Y) = X \beta \in \mathcal{C}(X)\) | \(E(\epsilon) \in \mathcal{C}(X)^\perp\) | |
\(Cov(Y) = \sigma^2 I\) | \(Cov(\epsilon) = \sigma^2 I\) |
- One-Way ANOVA
$
\[\begin{alignat}{4} y_{ij} &= \mu_i &&+ \epsilon_{ij} \\ &= E(y_{ij}) &&+ \epsilon_{ij} \\ &= \mu + \alpha_i &&+ \epsilon_{ij} \\ \\\ \bar \mu &= \mu + \bar \alpha_+ \\ \mu_1 - \mu_2 &= \alpha_1 - \alpha_2 \end{alignat}\] $
the parameters in the two models are different, but they are related.
- Simple Linear Regression
$
\[\begin{alignat}{4} y_i & = \beta_0 + \beta_1 x_i &&+\epsilon_i \\ & = E(y_i) &&+\epsilon_i \\ & = \gamma_0 + \gamma_1(x_i - \bar x) &&+\epsilon_i \end{alignat}\] $
$
\[\begin{alignat}{2} \mathcal{C}(X_1) = \mathcal{C}(X_2) \; \; \Longrightarrow \; \;\; \; \; X_1 &= X_2 T \\ X_1 \beta_1 &= X_2 T \beta_1 && = X_2 \beta_2 \\ & &&= X_2 (T \beta_1 + \nu), \; \; \; \forall\nu \in \mathcal{C}(X_2')^\perp \end{alignat}\] $
※ Note: A unique parameterization for \(X_j, \; j=1,2\) occurs \(\iff\) \(X_j ' X_j\) is nonsingular.
- Exercise: Show that a unique parameterization for \(X_j, \; j=1,2\) means \(\mathcal{C}(X_2 ' )^\perp = \{0\}\).
6.5.2 Testing Models
Consider
$ Y=X + , ; ; ; ; ; N(0, ; I_n) $
let’s partition \(X\) into $X = \[\begin{pmatrix} X_0, & X_1 \end{pmatrix}\]: ; (X_0) (X) $
$ \[\begin{alignat}{2} Y &= X_0 \beta_0 + X_1 \beta_1 &&+ \epsilon \tag{Full Model, FM} \\ Y &= X_0 \gamma &&+ \epsilon \tag{Reduced Model, RM} \end{alignat}\] $
이때 Hypothesis testing procedure can be described as \(H_0:\) Reduced Model, \(H_1:\) Full Model. (Example 3.2.0: pp. 52–54).
Let \(M\) and \(M_0\) be the orthogonal projection onto \(\mathcal{C}(X)\) and \(\mathcal{C}(X_0)\) respectively.
Note that with \(\mathcal{C}(X_0) \subset \mathcal{C}(X)\), \(M - M_0\) is the orthogonal projection onto the orthogonal complement of \(\mathcal{C}(X_0)\) with respect to \(\mathcal{C}(X)\), that is,
$ \[\begin{align} \mathcal{C}(X_0)_{\mathcal{C}(X)}^\perp &= \mathcal{C}(M - M_0) \\ &= \mathcal{C}(M \cap M_0^\perp ) \\ \\\ \hat\mu &= \hat E(Y) = MY \tag{under FM} \\ \hat\mu_0 &= \hat E(Y) = M_0 Y \tag{under RM} \end{align}\] $
If RM is true, then \(MY-M_0 Y = (M - M_0)Y\) should be reasonably small. Note that \(E(M-M_0)Y = 0\).
The decision about whether RM is appropriate hinges on deciding whether the vector \((M - M_0)Y\) is large.
The size of \((M - M_0)Y\)’s obvious measure is \([(M - M_0)Y]'[(M - M_0)Y] = Y'(M-M_0)Y\).
The size of \((M - M_0)Y\)’s reasonable measure is given by \(\dfrac{Y'(M-M_0)Y}{r(M-M_0)}\).
- ※ Note that $E ( ) = ^2 + $.
- Theorem 3.2.1.
Consider
$ Y=X + , ; ; ; ; ; N(0, ; I_n) , ; ; ; ; ; (X_0) (X) \
\ \
\[\begin{alignat}{2} Y &= X_0 \beta_0 + X_1 \beta_1 &&+ \epsilon \tag{Full Model, FM} \\ Y &= X_0 \gamma &&+ \epsilon \tag{Reduced Model, RM} \end{alignat}\]
$
$
\[\begin{alignat}{2} \dfrac {\dfrac{Y'(M-M_0)Y}{r(M-M_0)}} {\dfrac{Y'(I-M)Y}{r(I-M)}} &= \dfrac {\dfrac{Y'(M-M_0)Y}{df_1}} {\dfrac{Y'(I-M)Y}{df_2}} &&\sim F \Bigg( df_1 , df_2, \dfrac{\beta' X' (M-M_0)X \beta }{2 \sigma^2} && \Bigg) \tag{Under the FM} \\ \\\ \\\ \dfrac {\dfrac{Y'(M-M_0)Y}{r(M-M_0)}} {\dfrac{Y'(I-M)Y}{r(I-M)}} &= \dfrac {\dfrac{Y'(M-M_0)Y}{df_1}} {\dfrac{Y'(I-M)Y}{df_2}} &&\sim F \big( df_1 , df_2, 0 && \big) \tag{Under the RM} \end{alignat}\]
$
- Note: Example 3.2.2.; pp. 58–59
$ \[\begin{alignat}{2} M-M_0 &= (I-M_0) &&-(I-M) \\ Y'(M-M_0)Y &= Y'(I-M_0)Y &&-Y'(I-M)Y \\ &= SSE_{RM} &&-SSE_{FM} \end{alignat}\] $
6.5.3 A Generalized Test Procedure
Assume that \(Y = X \beta + \epsilon\) is correct. Want to test the adequacy of a model \(Y = X_0 \gamma + Xb + \epsilon\), where \(\mathcal{C}(X_0) \subset \mathcal{C}(X)\) and some known vector \(Xb=\) offset.
- Example 3.2.3.; Multiple Regression
$ Y = _0 J + _1 X_1 + _2 X_2 + _3 X_3 + $
want to test \(H_0: \beta_2 = \beta_3+5, \; beta_1 = 0, \cdots\).
$ \[\begin{alignat}{2} Y &= X \beta && &&+ \epsilon \tag{FM} \\ Y^\ast &\equiv Y && - X b && \\ &=X \beta && - Xb &&+ \epsilon \\ &=X (\beta && - b) &&+ \epsilon \\ &=X \beta^\ast && &&+ \epsilon \tag{FM} \\ \\\ \\\ Y &= X_0 \gamma && + Xb &&+ \epsilon \tag{RM} \\ Y^\ast &\equiv Y && && && - X b \\ &=X \gamma && &&+ \epsilon \tag{RM} \end{alignat}\]\end{alignat} $
In addition, when \(Y^\ast = Y_\ast\),
$
\[\begin{alignat}{2} \dfrac {\dfrac{ Y_\ast ' (M-M_0) Y_\ast }{ r(M-M_0)}} {\dfrac{ Y_\ast ' (I-M) Y_\ast }{r(I-M)}} &\sim F \Big( r(M-M_0), r(I-M), \delta^2 \Big) \\ \\ \delta^2 &=\dfrac{1}{2 \sigma^2} \Big( {\beta^\ast} ' X ' (M-M_0) X \beta^\ast \Big) \tag{non-centrality parameter} \end{alignat}\] $
$
\[\begin{alignat}{2} 0 &= \beta_\ast ' X' &&(M-M_0) X \beta_\ast \\ &\Updownarrow \\ 0 &= &&(M-M_0)X \beta_\ast \\ &\Updownarrow \\ X\beta & = M_0 (X &&\beta - X b) + Xb \tag{3} \end{alignat}\]
$
- will hold if
$ \[\begin{align} \gamma &= (X_0 ' X_0)^- X_0(X \beta - Xb) \\ &= (X_0 ' X_0)^- X_0 X \beta_\ast \end{align}\]
$
Furthermore,
$ \[\begin{alignat}{2} Y_\ast ' (M-M_0)Y_\ast &= Y_\ast ' (I-M_0)Y_\ast &&- &&Y_\ast ' (I-M)Y_\ast \; \; \; \; \;\text{ , and } \\ Y ' (I-M)Y &= && && Y_\ast ' (I-M)Y_\ast \end{alignat}\]
$
6.5.4 Testing Linear Parametric Functions
\(H_0: Y= X \beta + \epsilon, \; \; \; \; \; \Lambda' \beta=0 \tag{1}\)
$ \[\begin{alignat}{2} \Lambda ' \beta = 0 \; \; \; &\iff \beta &&\in \mathcal{N}(\Lambda ') = \mathcal{C}(X)^\perp \\ &\iff \beta \perp \mathcal{C}(\Lambda) \\ &\iff \beta \perp \mathcal{C}(\Gamma) \; \; \; \; \; \; \; \; \; \; &&\text{ if } \exists\Gamma \; \; s.t. \; \mathcal{C}(\Gamma) = \mathcal{C}(\Lambda) \\ &\iff \beta \perp \mathcal{C}(U) &&\text{ if } \exists U \; \; s.t. \; \mathcal{C}(U) = \mathcal{C}(\Lambda)^\perp \\ &\iff \beta = U_\gamma && \exists \gamma \tag{2} \end{alignat}\]
$
Thus, letting \(X_0 = XU\), (in general, \(\mathcal{C}(X_0) \subset \mathcal{C}(X)\)), then
$ \[\begin{alignat}{2} Y &= X \beta &&+ \epsilon \\ &= X U \gamma &&+ \epsilon \\ &= X_0 \gamma &&+ \epsilon \tag{3} \end{alignat}\]
$
Suppose \(\mathcal{C}(X_0) = \mathcal{C}(X)\). Then there is nothing to test and \(\Lambda' \beta = 0\) involves only arbitrary side conditions that do not affect the model. (EXAMPLE 3.3.1. pp. 62–64)
$ ’ ; ; ; ; ; ; P:= X’ P $
$
\[\begin{align} \mathcal{C}(MP) &\equiv \mathcal{C}(M-M_0) \\ &= \mathcal{C}(X-X_0) \\ &= \mathcal{C}(X) \; \cap \; \mathcal{C}(X_0)^\perp\\ &= \mathcal{C}(X_0)_{\mathcal{C}(X)}^\perp \end{align}\] $
thus, its distribution for testing \(H_0: \Lambda ' \beta = 0\) is given by
$
\[\begin{alignat}{2} \dfrac {\dfrac{Y'(M_{MP})Y}{r(M_{MP})}} {\dfrac{Y'(I-M)Y}{r(I-M)}} &\sim F \Big( r(M_{MP}), r(I-M), \delta^2 \Big) \tag{5} \\ \\\ \delta^2 &= \beta ' X' M_{MP}X \beta \tag{non-centrality parameter} \end{alignat}\]
$
- Proposition 3.3.2
$
\[\begin{alignat}{2} \mathcal{C}(M-M_0) &= \mathcal{C}(X_0)_{\mathcal{C}(X)}^\perp \\ &= \mathcal{C}(XU)_{\mathcal{C}(X)}^\perp = \mathcal{C}(MP) \end{alignat}\]
$
$
\[\begin{alignat}{2} H_0: Y=X\beta + \epsilon, \; \; \; \; \; \Lambda ' \beta = 0 \\ \Updownarrow \\ H_0: Y=X\beta + \epsilon, \; \; \; \; \; P'X \beta = 0 \\ \Updownarrow \\ H_0: Y=X\beta + \epsilon, \; \; \; \; \; P'MX \beta = 0 (\because MX = X) \\ \Updownarrow \\ E(Y) \in \mathcal{C}(X), \; \; \; \; E(Y) \perp \mathcal{C}(MP) \\ \Updownarrow \\ E(Y) \in \mathcal{C}(X) \; \cap \; \mathcal{C}(MP)^\perp, \; \; \; \; \mathcal{C}(X_0)=\mathcal{C}(X) \; \cap \; \mathcal{C}(MP)^\perp = \mathcal{C}(MP)^\perp_{\mathcal{C}(X)} \Longrightarrow \mathcal{C}(X_0)^\perp_{\mathcal{C}(X)} = \mathcal{C}(MP) \\ \Updownarrow \\ X_0 = (I-M_{MP})X \end{alignat}\]
$
$
\[\begin{align} \mathcal{C} \Big[ (I-M_{MP})X \ \Big] &= \mathcal{C} (X) \; \cap \; \mathcal{C} (MP)^\perp \\ &= \mathcal{C} (X) \; \cap \; \mathcal{C} (P)^\perp \tag{EXAMPLE 3.3.4.: pp.66–67} \end{align}\] $
let \(\Lambda ' \beta\) is estimable, i.e., \(\Lambda = X'P\). then \(\mathcal{C}(\Lambda) = \mathcal{C}(X'P) =\mathcal{C}(MP)\), and \(X \hat \beta = MY\), and \(\Lambda ' \hat \beta = P' X \hat \beta = P' M Y\). then
$
\[\begin{align} Y' M_{MP}Y &= Y' M && (P' M P)^- && MPY \\ &= \hat \beta ' \Lambda && [P' X(X'X)^-X' P]^- && \Lambda ' \hat \beta \\ &= \hat \beta ' \Lambda && [\Lambda' (X'X)^- \Lambda]^- && \Lambda ' \hat \beta \end{align}\]
$
이윗부분 전혀모르겠음
thus,
$ \[\begin{align} (5) = \dfrac{\dfrac{\hat \beta ' \Lambda [\Lambda ' (X'X)^- \Lambda]^- \Lambda' \hat \beta}{r(\Lambda)}}{MSE} &\sim F \Big( r(MP), r(I-M), \delta^2 \Big)\\ \\\ \\\ \delta^2 &= \dfrac{\hat \beta ' \Lambda [\Lambda ' (X'X)^- \Lambda]^- \Lambda' \hat \beta}{2 \sigma^2} \\ Cov\Big(\Lambda ' \hat \beta \Big) &= \sigma^2 \Lambda ' (X' X)^{-} \Lambda \end{align}\]\end{align} $
For \(H_0: \lambda ' \beta =0, \; \; \; \lambda \in \mathbb{R}^p\),
$
\[\begin{align} Y'M_{MP}Y &= \hat \beta ' \lambda \big [\lambda ' (X'X)^- \lambda \big]^- \lambda' \hat \beta \\ &=\dfrac{\big( \lambda' \hat \beta \big)^2}{\lambda'(X'X)^-\lambda} \end{align}\]
$
and, under \(H_0: \lambda ' \beta =0\),
$ F = (5) = F ( 1, ; r(I-M) ) $
- Definition 3.3.5.
The condition \(E(Y) \perp \mathcal{C}(MP)\) is called the constraint by \(\Lambda ' \beta = 0\) where \(\Lambda = X' P\). in other words, \(\mathcal{C}(MP)\) is the constraint by \(\Lambda ' \beta = 0\).
- Do Exercise 3.5:
Show that a necessary and sufficient condition for \(\rho_1 ' X \beta = 0\) and \(\rho_2 ' X \beta = 0\) to determine the orthogonal constraints on the model is that \(\rho_1 ' X \rho_2 = 0\)
6.5.5 Theoretical Complements
Consider testing \(\Lambda ' \beta = 0\) when \(\Lambda ' \beta\) is NOT estimable.
let \(\Lambda_0 ' \beta\) be estimable part of \(\Lambda ' \beta\).
\(\Lambda_0\) is chosen, so that \(\mathcal{C}(\Lambda_0) = \mathcal{C}(\Lambda) \; \cap \; \mathcal{C}(X')\), which means that \(\Lambda ' \beta = 0\) implies that \(\Lambda_0 ' \beta = 0\) but \(\Lambda_0 ' \beta\) is estimable, because \(\mathcal{C}(\Lambda_0) \subset \mathcal{C}(X')\).
- Theorem 3.3.6.
let \(\mathcal{C}(\Lambda_0) = \mathcal{C}(\Lambda) \; \cap \; \mathcal{C}(X')\) and \(\mathcal{C}(U_0) = \mathcal{C}(\Lambda_0)^\perp\). Then \(\mathcal{C}(XU) = \mathcal{C}(XU_0)\). Thus \(\Lambda ' \beta = 0\) and \(\Lambda_0 ' \beta = 0\) induce the same RM.
- Proposition 3.3.7.
let \(\Lambda_0 ' \beta\) be estimable and \(\Lambda \not = 0\). then \(\Lambda ' \beta = 0 \; \; \Longrightarrow \; \; \mathcal{C}(XU) \not = \mathcal{C}(X)\).
- Corollary 3.3.8.
$
(_0) = () ; ; (X’) = {0 }
\
\
(XU) ; ; (X)
$
6.5.6 A Generalized Test Procedure
Consider as below, whose column space is solvable.
\(H_0: \Lambda' \beta = d, \; \; \; \; \; d \in \mathcal{C}(X'), \; \; \; \; \Lambda' b =d\)
$ \[\begin{alignat}{2} \Lambda ' \beta = \Lambda ' b = d \; \; \; &\iff \Lambda ' (\beta - b) &&= 0 \\ &\iff (\beta - b) &&\perp \mathcal{C}(\Lambda) \\ &\iff (\beta - b) &&\in \mathcal{C}(U) \; \; \; \; \; \; &&\text{where } \; \mathcal{C}(U) = \mathcal{C}(\Lambda)^\perp \\ &\iff (\beta - b) &&= U_\gamma &&\exists \gamma \\ &\iff X\beta - Xb &&= XU_\gamma \\ & \; \; \; \Updownarrow \\ X\beta &= XU_\gamma + Xb, \\ Y &= X \beta + \epsilon \\ &= X U_\gamma + Xb + \epsilon \\ &= X_0 \gamma + Xb + \epsilon, && && \text{where } \; X_0 = XU \end{alignat}\]
$
if \(\Lambda = X'P\), then \(\mathcal{C}(X_0)_{\mathcal{C}(X)}^\perp = \mathcal{C}(MP)\) and its test statistics is
$ \[\begin{align} F = \dfrac {\dfrac{(Y-Xb)'M_{MP}(Y-Xb)}{r \Big(M_{MP} \Big)}} {\dfrac{(Y-Xb)'(I-M)(Y-Xb)}{r \Big(I-M \Big)}} = \dfrac {\dfrac{(\Lambda ' \hat \beta - d)' \Big[ \Lambda'(X'X)^{-}\Lambda \Big]^- (\Lambda ' \hat \beta - d)}{r(\Lambda)}} {MSE} \sim F(?, ?, ?) \end{align}\] $
- Remark: (EXAMPLE 3.3.9.: pp.71–72, EXAMPLE 3.4.1.: pp.75)
If \(\Lambda ' \beta = d\), the same reduced model results if we take \(\Lambda ' \beta = d_0\), where \(d_0 = d + \Lambda ' \nu\) and \(\nu \perp \mathcal{C}(X')\). Note that, in this construction, if \(\Lambda ' \beta = d\) is estimable, \(d_0 = d\) for any \(\nu\).
6.5.7 Testing Single Degrees of Freedom in a Given Subspace
$ RM: Y=X_ 0 + ; ; ; ; ; vs. ; ; ; ; ;
FM: Y=X + , ; ; ; ; ; with; ; (X_0) (X)
$
let \(M_\ast = M - M_0\), consider \(H_0 : \Lambda ' \beta = 0\).
if \(\Lambda = X'P\), i.e. \(\Lambda \in \mathcal{C}(X')\), then \(M_\ast = M_{MP}\).
- Proposition 3.3.2
Since \(M M_\ast = M_\ast\),
$
\[\begin{align} &\mathcal{C}(M - M_0) = \mathcal{C}(X_0)_{\mathcal{C}(X)}^\perp \equiv \mathcal{C}(XU)_{\mathcal{C}(X)}^\perp = \mathcal{C}(MP) \\ \Longrightarrow \; \; \; &M \rho \in \mathcal{C}(M_\ast) \\ \Longrightarrow \; \; \; &M \rho = M_\ast M \rho = M_\ast \rho \\ \Longrightarrow \; \; \; &\rho ' \hat \beta = \rho ' M_\ast Y = \rho ' M Y \end{align}\] $
thus the test statistic for \(H_0 : \Lambda ' \beta = 0\) is
$
=
$
6.5.8 Breaking SS into Independent Components
Consider \(X = \begin{pmatrix} X_0, & X_1 \end{pmatrix}\). set
$
\[\begin{alignat}{2} &SSR(X_1 \vert X_0) &&\equiv Y ' (M-M_0)Y && \tag{Sum of Squares for regression X1 after X0}\\ &SSR(X) &&\equiv Y ' MY \\ &SSR(X_0) &&\equiv Y ' M_0 Y \\ &SSR(X) &&= SSR(X_0) &&+ SSR (X_1 \vert X_0) \end{alignat}\] $
- Note: if \(\epsilon \sim N(0, \; \sigma I)\), then \(SSR(X_0) \perp SsR(X_1 \vert X_0)\).
6.5.9 General Theory
Let \(M\) and \(M_\ast\) be the orthogonal projection operator into \(\mathcal{C}(X)\) and \(\mathcal{C}(X_\ast)\) respectively. Then, with \(\mathcal{C}(X_\ast) \subset \mathcal{C}(X)\), \(M_\ast\) defines a test statistic as below.
$
{} {}
; ; ; :Y = X_+
$
$ \[\begin{align} &I-(M-M_\ast ) &&= (I-M) + M_\ast \\ &\mathcal{C}(M-M_\ast) &&:\tag{Estimation Space, under H0} \\ &\mathcal{C}(M_\ast) &&:\tag{Test Space, under H0} \\ &\mathcal{C} \Big(I - (M-M_\ast)\Big) &&:\tag{Error Space, under H0} \end{align}\]
$
Using Gram-Schmidt procedure, let’s construct \(M_\ast\) so that
$
M_= RR’ = {i=1}^r R_iR_i ’ = {i=1}^r M_i, ; ; ; ; ; R=(R_1 , , R_r)
$
and \(M_i M_j=0\) for \(i \not = j\). By Theorem 1.3.7,
$ Y’M_i Y Y’M_j Y ; ; ; ; ; ; M_i M_j =0 $
Next, $ Y’M Y = _{i=1}^r Y’M_i Y $, therefore when \(r(M_i)=1\),
$
{} {}
F ( 1, r(I-M), ’ X’ M_i X )
$
$
\[\begin{alignat}{2} & && && &&\beta ' X' M_\ast X \beta \; \; &&= \; \; \sum_{i=1}^r \beta ' X' M_i X \beta && =0 \; \; \; \\ &\iff && && \forall i \; \; : \; \; && \beta ' X' M_i X \beta && &&=0 \\ &\iff && &&\forall i \; \; : \; \; &&R_i ' X \beta && &&= 0 \\ &\iff && && &&H_0 \text{ is true.} \end{alignat}\] $
- EXAMPLE 3.6.1.: Balanced design; pp.79–80
- EXAMPLE 3.6.2.: Unbalanced design;pp.80–81
6.5.10 Two-Way ANOVA
$ \[\begin{alignat}{2} y_{ijk} &= \mu + \alpha_i + \eta_j &&+ \epsilon_{ijk} \tag{FM} \\ y_{ijk} &= \mu + \alpha_i &&+ \epsilon_{ijk} \tag{RM} \end{alignat}\] $
$ \[\begin{align} M &= M_\mu + M_\alpha + M_\eta \\ Y'(M-M_0)Y &= R(\eta \; \Big \vert \; \alpha, \; \mu) \tag{1} \end{align}\] $
- Reduction in SSE, due to fitting \(\eta_j\)’s after \(\mu\) and \(\alpha_i\)’s.
Next,
$
\[\begin{alignat}{2} y_{ijk} &= \mu + \alpha_i &&+ \epsilon_{ijk} \tag{FM} \\ y_{ijk} &= \mu &&+ \epsilon_{ijk} \tag{RM} \\ \\\ \\\ Y'(M_0-M_J)Y &= R(\alpha \; \Big \vert \; \mu) \\ Y'(M-M_J)Y &= R(\alpha, \; \eta \; \Big \vert \; \mu) \\ &= R(\eta \; \Big \vert \; \mu, \; \alpha) &&+ R(\alpha \; \Big \vert \; \mu) \end{alignat}\]
$
In general,
$
\[\begin{alignat}{2} R(\eta \; \Big \vert \; \alpha, \; \mu) &\not = R(\eta \; \Big \vert \; \mu) \\ R(\alpha \; \Big \vert \; \eta, \; \mu) & \not = R(\alpha \; \Big \vert \; \mu) \end{alignat}\]
$
In paricular, for balanced design, if \(\mathcal{C}(X_\alpha) \perp \mathcal{C}(X_\eta)\),
$
\[\begin{alignat}{2} R(\eta \; \Big \vert \; \alpha, \; \mu) & = R(\eta \; \Big \vert \; \mu) \\ R(\alpha \; \Big \vert \; \eta, \; \mu) & = R(\alpha \; \Big \vert \; \mu) \end{alignat}\]
$
- Proposition 3.6.3.
$
\[\begin{alignat}{2} R(\eta \; \Big \vert \; \alpha, \; \mu) & = R(\eta \; \Big \vert \; \mu) \; \; \; \; \; &&\iff \; \; \; \; \; \mathcal{C}(X_1 - M_j) \perp \mathcal{C}(X_0 - M_j) \\ \text{that is}\; \; \; \; \; \; \; M_1 - M_J& = M-M_0 \; \; \; \; \; &&\iff \; \; \; \; \; (M_1 - M_J)(M_0 - M_J) = 0, \; \; \; \; \; \text{where} \; &&R(\eta \; \Big \vert \; \alpha, \; \mu) &&= Y'(M-M_0)Y \\ & && && R(\eta \; \Big \vert \; \mu) &&= Y'(M_1 -M_0)Y \end{alignat}\]
$
6.5.11 Confidence Regions
\(100(1-\alpha)\%\) Confidence Region(CR) for \(\Lambda ' \beta\) consists of all the vectors \(d\) satisfying the inequality
$
{} {MSE}
( 1- , ; r(), ; r(I-M) )
$
These vectors form an ellipsoid in \(r(\Lambda)\)-dimensional space.
For regression problems, if we take \(P' = (X'X)^{-1}X'\), then \(\Lambda'\beta = P' X \beta = \beta = d\).
The \(100(1-\alpha)\%\) CR is
$ \[\begin{alignat}{2} & \dfrac {\dfrac{\Big[\Lambda ' \hat \beta - d\Big]' \Big[\Lambda ' (X'X)^- \Lambda\Big]^- \Big[\Lambda ' \hat \beta - d\Big]}{r(\Lambda)}} {MSE} \; \; \; && = \; \; \; & \dfrac {\dfrac{\Big(\hat \beta - \beta \Big)' \Big( X'X \Big)\Big(\hat \beta - \beta \Big)} {p}} {MSE} \; \; \; &&\le \; \; \; \Big( 1- \alpha, \; p, \; n-p \Big) \end{alignat}\]
$
6.5.12 Tests for Generalized Least Squares Models
$ \[\begin{alignat}{4} &Y &&= &&X \beta &&+ &&\epsilon \; \; \; \; \; &&vs. \; \; \; \; \; &&Y = &&X_0 \beta_0 &&+ &&\epsilon , \; \; \; \; \; && \epsilon \sim N(0, \; \sigma^2 V) \tag{1} \\ & && && && && && \Updownarrow \\ Q^{-1}&Y &&= Q^{-1} &&X \beta &&+ Q^{-1} &&\epsilon \; \; \; \; \; \; \; \; \; &&vs. \; \; \; \; \; Q^{-1} &&Y = Q^{-1} &&X_0 \beta_0 &&+ Q^{-1} &&\epsilon , \; \; \; \; \; Q^{-1} && \epsilon \sim N(0, \; \sigma^2 I) \tag{2} \end{alignat}\] $
test (1) and (2) is equal.
- Note: \(\mathcal{C}(Q^{-1}X_0) \subset \mathcal{C}(Q^{-1}X)\).
From Section 2.7,
$ \[\begin{align} A &= X(X'V^{-1}X)^- X' \ast V^{-1} \\ \\ MSE &= \dfrac{Y' (I-A)' V^{-1} (I-A)Y}{n-r(X)} \\ \\ A_0 &= X_0(X_0'V^{-1}X_0)^- X_0' \ast V^{-1} \end{align}\] $
- Theorem 3.8.1
$ \[\begin{align} \dfrac{\dfrac{Y' (A-A_0) V^{-1} (A-A_0)Y}{r(X) - r(X_0 )}}{MSE} &\sim F \Big( r(X)-r(X_0), \; n-r(X) , \; \delta^2 \Big) \\ \\ \delta^2 &= \dfrac{\beta ' X' (A-A_0) V^{-1} (A-A_0)X \beta}{2\sigma^2} \tag{1} \\ \\ \\\ {\beta ' X' (A-A0) V^{-1} (A-A_0)X \beta} \; \; \; \; \; &\iff \; \; \; \; \; E(Y) \in \mathcal{C}(X_0) \tag{2} \end{align}\] $
- Theorem 3.8.2
let \(\Lambda ' \beta\) be estimable. then the test statistic for \(H_0 : \Lambda ' \beta = 0\) is
$ \[\begin{align} \dfrac{\dfrac{\hat \beta ' \Lambda \Big[ \Lambda ' (X'V^{-1}X)^- \Lambda \Big]^- \Lambda ' \hat \beta}{r(\Lambda)}}{MSE} &\sim F \Big( r(\lambda), \; n-r(X) , \; \delta^2 \Big) \\ \\ \delta^2 &= \dfrac{\beta ' \Lambda \Big[ \Lambda ' (X'V^{-1}X)^- \Lambda \Big]^- \Lambda ' \beta}{2\sigma^2} \tag{1} \\ \\ \\\ {\beta ' \Lambda \Big[ \Lambda ' (X'V^{-1}X)^- \Lambda \Big]^- \Lambda ' \beta} \; \; \; \; \; &\iff \; \; \; \; \; \Lambda ' \beta = 0\tag{2} \end{align}\] $
- Theorem 3.8.3
$ \[\begin{align} \dfrac{Y' (A-A_0) V^{-1} (A-A_0)Y}{\sigma^2} &\sim \chi^2\Big(r(x) - r(X_0), \; \delta^2 \Big) \\ \\ \delta^2 &= \dfrac{\beta ' X' (A-A_0) V^{-1} (A-A_0)X \beta}{2\sigma^2}, \\ \\ \sigma^2 = 0 \; \; \; \; \; &\iff E(Y) \in \mathcal{C}(X_0) \tag{1} \\ \\ \\\ \dfrac{\hat \beta ' \Lambda \Big[ \Lambda ' (X'V^{-1}X)^- \Lambda \Big]^- \Lambda ' \hat \beta}{2\sigma^2} &\sim \chi^2 \Big( r(\Lambda) , \; \delta^2 \Big) \\ \\ \delta^2 &= {\hat \beta ' \Lambda \Big[ \Lambda ' (X'V^{-1}X)^- \Lambda \Big]^- \Lambda ' \hat \beta}, \\ \\ \sigma^2 = 0 \; \; \; \; \; &\iff \Lambda ' \beta = 0 \tag{2} \end{align}\] $